PENGEMBANGAN RPP DAN LKS PADA MATERI POKOK TRIGONOMETRI MELALUI PENERAPAN MODEL DISCOVERY LEARING UNTUK SMA/MA - Sarah, Shanti; Anggraini, Rini Dian; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is by the limited availability of mathematics learning instrument based curicullum 2013 by teachers. This research purpose is produce to mathematics learning instrument (Lesson Plan and Student Worksheet) which refers to Discovery Learning model on matter of build trigonometri for SMA/MA with minimum valid and practical criteria. This reserch method used is ADDIE model by Dick & Carry, that consist of analysis, design, development, implementation and evaluation, but the reserch only done to implementation step due to time and cost constraints. In this research, a limited trial was conducted on 17 students of high school class XI.. Based on the results, data analysis can be concluded that the study of mathematics is very valid to the average ratings for the lesson plan is 3.71 and the average ratings for the student worksheet is 3.52. The student worksheet has also reached the practical qualification in mean percentage of student responses 94,58% in limited group trial with very practical criteria. Based on the results of this study can be concluded that the product in the form of RPP and LKS mathematics with discovery learning model on Trigonometry material for SMA / MA is considered very valid and practical.Keywords: Discovery Learning model, Lesson Plan, Students worksheet, Trigonometry